Alcohol use among reserve-dwelling adult First Nation members: Use, problems, and intention to change drinking behavior. (February 2015) - Spillane, Nichea S.; Greenfield, Brenna; Venner, Kamilla; Kahler, Christopher W.
Abstract: Introduction: Although alcohol use was not part of traditional First Nation (FN) life, alcohol misuse currently poses a significant public health problem. There is a dearth of research efforts to understand both alcohol misuse and efforts to resolve these problems. The primary aims of this study were to 1) present descriptive data on alcohol use in FN adults living on one reserve in Eastern Canada; and 2) explore correlates of help seeking intentions and past behaviors. Methods: We administered questionnaires to 211 FN people (96 men; 113 women; 2 unknown). Results: Nearly two-thirds of our sample were current drinkers (N = 150). Of those, 29% endorsed they needed help with their drinking, and half reported that they would probably try to cut down or stop drinking in the next year. Multiple regression analyses suggested that drinking was positively associated with a greater perceived need for help with drinking ( β = .40, p = < .001). Lower scores on a measure of cultural identity (i.e., stronger FN identity) was associated with a greater perceived need for help with drinking ( β = − .18, p = .04). Greater endorsement of past year attempts to stop drinking ( β = .33, p < .001) and higher alcohol reduction expectancies ( β = .43, p < .00) were positively associated and lower scores on cultural identity (i.e., stronger FN identity) ( β = − .19, p = .03) was associated with trying to cut down or stop drinking in the next year. Conclusions: Future research should explore the nature of cultural identity as a protective factor. Highlights: Alcohol use among First Nation members is a problem. Cultural identity is associated with perceived need for help with alcohol use. Cultural identity is associated with intentions to change alcohol use.